Education in Health From an Islamic Perspective Through Health Checks and Physical Fitness Development in State Elementary School 002 Kelarik, Bunguran Utara - Khair, Fathul; Larasati, Diah Ratri (Society : Jurnal Pengabdian Masyarakat, 2025)
This community service activity focused on health education from an Islamic perspective through health screenings and physical fitness and activity  at  Elementary School 002 Kelarik. The program aimed to enhance elementary school students' understanding of health maintenance while promoting healthy lifestyles and assessing their physical condition. The activity was designed to provide comprehensive understanding from both medical and Islamic perspectives regarding the importance of maintaining health. The target participants were 50 students from grades IV, V, and VI of Elementary School 002 Kelarik. The methods employed included lectures, discussions, health examinations, and physical fitness and activity. The implementation phase involved education about the importance of healthy living behaviors through lectures and discussions, followed by vital signs examination, nutritional status assessment, and physical fitness and activity. Through this health education and physical physical fitness and activity help children understand healthy lifestyle behaviors and encourage regular physical activity, ultimately preventing health issues among school children.